Game Edukasi Introduksi Bilangan dan Operasi Aritmatika dengan Penerapan Algoritma Fisher–Yates Shuffle - Athariq Rifki Yanda; Reva Ragam Santika; Anita Diana; Retno Wulandari (Universitas Bandar Lampung (UBL), 2022)
The introduction of numbers and arithmetic operations is basic learning in Mathematics aimed at students at the kindergarten level, where the learning method is still conventional and tedious. The solution that can be applied is to use an android educational game using the Fisher-Yates Shuffle method. useful in obtaining random permutations of a series of questions that allow the arrangement of similar questions to be impossible to appear again while avoiding students remembering the questions and their answers. The idea of making games is to create a new impression and make it easier to learn the introduction of numbers and arithmetic operations. The technique used is Game Development Life Cycle and Android-based Unity 3D software in the development of this educational game application. The application of the concept of User-Centered Design (UCD) is used in the evaluation in measuring game excellence with a Playability testing approach in the form of 4 criteria, namely gameplay, usability, mobility, and game story. The questionnaire was filled out by 10 respondents, namely kindergarten students with the assistance of their parents. Based on the assessment, it is determined that this game gets a score where gameplay is 75%, usability is 75%, mobility is 70%, and the game story is 70%. support kindergarten students in learning number introduction and arithmetic operations.